ANALISIS VARIASI GAYA MENGAJAR GURU MATA PELAJARAN IPS KELAS VII DI SMP MUHAMMADIYAH 1 PONTIANAK - Tarmizi, Isa; Sumartono, Bambang Genjik; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Purpose of this research is to learn about The Social Study Teacher?s Teaching Style Variation in Seventh Grade Class of Muhamadiah 1 Junior High Pontianak. The problem arise in this research is how varied social study teacher teach? and How The Teacher of Social Study Class of Muhammadiah 1 Junior High Pontianak choose and moving to better position in class while teaching the Seventh Grader?. The variable used to measure in this research is single variable which is ?Teacher?s teaching variation?. The source of this research is the teacher of Seventh Grade Class of Muhammadiah 1 Junior High Pontianak. The method used in this research is descriptive Method in the from of Case Study. The data is obtained through live observation, interview, and study documentation. Toanalyze the data, this research used one of the Descriftive analysis, which is the Descriptive Qualitative Analysis. The research shown reasecher obtained compared to the criteria of analysis in teaching variation which consist of voice variation, focusing student?s attention, pausing, field of view, gestures and how to positioning, The Social Study teacher is already good, however there?s a weakness. At Focusing te teach important study Material, the teacher is still weak in that part. Keyword: Teacher?s, Teaching Style Variation